Oxford Dictionary of Computing / For Learners of English - Pyne Sandra; Tuck Allene (Oxford University Press, 1996)
An exciting new dictionary for computer users and people who study computing. Preface and User's Guide to the Dictionary, The Dictionary, Appendices, Core Vocabulary, ASCII characters in decimal and hexadecimal, Numeric Equivalents, Key to the Dictionary.